Penguatan Legalitas Usaha dan Pembuatan Katalog Produk Untuk Keberlangsungan Bisnis UMKM - Sunnah, Vinna Kusuma; Dewi, Nurma Gupita (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2024)
The "Kity Chicken" business is a Micro, Small and Medium Enterprises (MSMEs) that was founded in 2021 by Mrs. Susilowati. This MSME is located in Japeledok Village Rt 05 / Rw 01 Pancur District, Rembang Regency, Central Java. The beginning of this business was founded by Mrs. Susi with her cooking skills and hobby of cooking which triggered her to start a chicken business. Mrs. Susi initially sold chicken at home but has now opened a chicken stall to sell. Based on a survey conducted at UMKM "Kity Chicken", the service team found problems including: not having business legality, and not having a product catalog or menu list. To solve these problems, the service team provides activity program solutions in the form of: 1) facilitate business legality, and 2) make a menu list or product catalog as one of the price transparency. The results of the community service program at UMKM "Kity Chicken" are: 1) UMKM "Kity Chicken" already has a Business Identification Number (NIB) so that its business is legal, and 2) UMKM "Kity Chicken" already has a menu list or product catalog to make it easier for buyers to choose an existing menu.